Post-national urbanity beyond (Pluri)Nation(al)-states in the EU: Benchmarking Scotland, Catalonia and the Basque Country - Calzada, I (Revista Culturales, 2016)
This article compares the three small nation cases of Scotland, Catalonia, and the Basque Country after 2014, a remarkable year for the European Union. Since the referendum on Scottish independence in September 2014, depending on its unique context, each cityregional small nation has engaged in democratic experimentation on the right to decide its future beyond its referential (pluri)nation(al)-states differently from the United Kingdom and Spain. Most recently, the Brexit referendum has triggered a deeper debate on how regional political claims by these European stateless small nations could re-scale the fixed (pluri)nation(al)-states’ structure and even directly affecting the European Union. The differences in each of these three cases is noteworthy; yet, even more substantial are their diverse means of accommodating strategic pathways of self-determination through political innovation processes among current pervasive responses to a growing ‘post-national urbanity’ pattern in the European Union: To what extent is the starting point of the smart devolution for each case similar? What are the potential political scenarios for them as a result of the de/recentralisation attitude of their referential (pluri)nation(al)-states? What are the most relevant strategic political innovation processes? This paper aims to benchmark how Scotland, Catalonia and the Basque Country are strategically moving forward beyond their referential (pluri)nation(al)-states in such a new European geopolitical pattern we can call ‘post-national urbanity’ by formulating devolution and even independence in unique terms. This paper is part of a broader research project entitled 'Benchmarking City-Regions'.